Rotifers from inland water bodies of continental Ecuador and Galápagos Islands: An updated checklist - López, Carlos; Soto, Luz Marina; Lafuente, Wilson; Stamou, Georgia; Michaloudi, Evangelia; Papakostas, Spiros; Fontaneto, Diego (Zootaxa, 2020)
We present an updated checklist of the rotifer fauna from inland aquatic habitats in continental Ecuador and the Galápagos islands based on published rotifer records found in the literature. The checklist summarizes the status of the current taxonomic and faunistic knowledge on rotifers in Ecuador, updates the nomenclature, and reports the regions where each species has been found in the country. A total of 287 valid species (269 monogononts and 18 bdelloids was found. The Ecuadorian region with the highest number of records was Amazonia (228) followed by the Coastal region (139) and the Andes (121), whereas in the Galápagos Archipelago only 40 species have been recorded. Studies of the rotifer fauna of the areas are scarce and quite recent, pointing to important gaps in our knowledge on taxonomy and biogeography of Ecuadorian rotifers.